A method for reducing the electrolysis temperature of an aluminum electrolysis cell
By adding magnesium carbonate to the aluminum electrolytic cell, the initial crystal temperature of the electrolyte is reduced, and the problem of deterioration of alumina solubility after reducing the electrolytic temperature in the prior art is solved, and a more stable electrolysis process and higher electrical energy utilization rate are achieved.
Patent Information
- Application Number
- CN202211033839.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-26
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2042-08-26
AI Technical Summary
The existing methods to reduce the electrolytic temperature of aluminum electrolytic cells will lead to poor solubility of aluminum oxide, affecting the stability of the electrolytic cells.
By adding magnesium carbonate and substances containing magnesium carbonate to the electrolytic cell, the primary crystal temperature of the electrolyte is reduced, thereby achieving the purpose of reducing the electrolytic temperature of the aluminum electrolytic cell.
It effectively reduces the electrolytic temperature of the aluminum electrolytic cell, improves the dissolution performance of the aluminum oxide, and improves the stability and power utilization of the electrolytic cell.
Smart Images

Figure CN115466988B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of aluminum electrolysis, and in particular to a method for reducing the electrolysis temperature of an aluminum electrolysis cell. Background Art
[0002] Due to the difference in electrolyte composition, the electrolysis temperature of electrolytic cells of different enterprises varies greatly, with the lowest electrolysis temperature being around 910°C and the highest reaching 965°C. Under the same other conditions, a 10°C reduction in electrolysis temperature can increase the current efficiency of industrial aluminum electrolytic cells by about 1.5% and the power utilization rate by about 0.7% on average. In addition, a reduction in electrolysis temperature can reduce fluoride volatilization and aluminum fluoride unit consumption, and can also reduce carbon anode oxidation and thus reduce anode consumption.
[0003] At present, the existing methods for reducing the temperature of the electrolytic cell mainly include adding A1F3 to the current electrolytic cell to reduce the molecular ratio or adding additives such as LiF, which can reduce the electrolyte initial crystallization temperature and reduce the aluminum electrolysis temperature while keeping the superheat unchanged. The above methods all affect the solubility and dissolution rate of A12O3 in the electrolyte. If the dissolution rate is too low, the A12O3 added to the electrolytic cell will not be dissolved and diffused in time, and precipitation will occur at the bottom of the cell, affecting the cell condition. Summary of the invention
[0004] The present application provides a method for reducing the electrolysis temperature of an aluminum electrolysis cell, so as to solve the technical problem that the solubility of aluminum oxide will be deteriorated in the existing method for reducing the electrolysis temperature of an aluminum electrolysis cell.
[0005] In a first aspect, the present application provides a method for reducing the electrolysis temperature of an aluminum electrolysis cell, the method comprising:
[0006] By adding additives into the electrolytic cell, the electrolysis temperature of the aluminum electrolytic cell can be reduced;
[0007] The additives include magnesium carbonate and substances containing magnesium carbonate.
[0008] Furthermore, the content of impurities in the substance containing magnesium carbonate is less than 8% by weight; and the impurities do not include aluminum oxide.
[0009] Furthermore, the substance containing magnesium carbonate includes at least one of magnesite and dolomite.
[0010] Furthermore, the additive reduces the electrolysis temperature of the aluminum electrolysis cell by reducing the initial crystallization temperature of the electrolyte.
[0011] Furthermore, the amount X of the additive added and the mass fraction Z of magnesium fluoride in the electrolyte after adding the additive satisfy equation 1; equation 1:
[0012] Z = X*C1*C2+Z1-Z2;
[0013] Among them, Z represents the amount of additive added; X represents the mass fraction of magnesium fluoride in the electrolyte after adding the additive; C1 represents the mass fraction of magnesium carbonate in the additive; C2 represents the conversion rate constant of each unit of magnesium carbonate into magnesium fluoride; Z1 represents the initial mass fraction of magnesium fluoride in the electrolyte; Z2 represents the mass fraction of magnesium fluoride volatilized in the electrolyte.
[0014] Furthermore, the value of C2 is 0.74; the value of Z2 is 0.001-0.003.
[0015] Furthermore, the amount of the additive X and the preset reduction value Y of the electrolysis temperature of the aluminum electrolysis cell satisfy the relationship 2:
[0016] Y=C*X*C1*C2
[0017] Among them, Y represents the preset reduction value of the electrolysis temperature of the aluminum electrolysis cell; C represents the constant of the reduction of electrolyte temperature caused by each unit increase of magnesium fluoride in the electrolyte; X represents the mass fraction of magnesium fluoride in the electrolyte after adding the additive; C1 represents the mass fraction of magnesium carbonate in the additive; C2 represents the conversion rate constant of each unit of magnesium carbonate into magnesium fluoride.
[0018] Furthermore, the value of C is 6 to 7; the value of C2 is 0.74.
[0019] Furthermore, the method of adding additives to the electrolytic cell to reduce the electrolysis temperature of the aluminum electrolytic cell specifically includes:
[0020] According to the preset reduction value Y of the electrolysis temperature of the aluminum electrolysis cell, the addition amount X of the additive is obtained;
[0021] Adding the additive in an amount X to the electrolytic cell in stages to reduce the electrolysis temperature of the aluminum electrolytic cell;
[0022] The amount of additive added once in each stage shall not exceed 0.15% of the total weight of the electrolyte; and the total amount of additive added in each stage shall not exceed 2.5% of the total weight of the electrolyte.
[0023] Furthermore, the preset reduction value Y of the electrolysis temperature of the aluminum electrolysis cell is less than 50.
[0024] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0025] The embodiment of the present application provides a method for reducing the electrolysis temperature of an aluminum electrolysis cell. On the basis of existing aluminum electrolysis process conditions, the method reduces the temperature of the electrolysis cell by adding at least one of magnesium carbonate and a substance containing magnesium carbonate to the electrolysis cell. The carbon dioxide produced by the decomposition of magnesium carbonate in the electrolysis cell can disturb the electrolyte, which is beneficial to the dissolution of aluminum oxide, thereby solving the problem that additives for reducing the temperature of the electrolysis cell will cause the solubility of aluminum oxide to deteriorate. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0027] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0028] Figure 1 A schematic flow chart of a method for reducing the electrolysis temperature of an aluminum electrolysis cell provided in Example 1 of the present application. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0030] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0031] Due to the difference in electrolyte composition, the electrolysis temperature of electrolytic cells of different enterprises varies greatly, with the lowest electrolysis temperature being around 910°C and the highest reaching 965°C. Under the same other conditions, a 10°C reduction in electrolysis temperature can increase the current efficiency of industrial aluminum electrolytic cells by about 1.5% and the power utilization rate by about 0.7% on average. In addition, a reduction in electrolysis temperature can reduce fluoride volatilization and aluminum fluoride unit consumption, and can also reduce carbon anode oxidation and thus reduce anode consumption.
[0032] At present, the existing methods for reducing the temperature of the electrolytic cell are mainly to add A1F3 to the current electrolytic cell to reduce the molecular ratio or add additives such as LiF, which can reduce the electrolyte initial crystallization temperature and reduce the aluminum electrolysis temperature while keeping the superheat unchanged.
[0033] Patent CN 1873057A "Production method for transition of aluminum electrolytic cell to low temperature electrolysis" proposes an electrolyte composition, wherein the molecular ratio, calcium fluoride, magnesium fluoride, and lithium fluoride are controlled within the range of 2.2-2.35, 3-6%, 1-4%, and 1.6-2.0%, respectively, the primary crystallization temperature is 905-915°C, and the electrolysis temperature is maintained at 915-930°C. This patent has poor solubility of alumina due to the low molecular ratio, and precipitation is easily formed at the bottom of the electrolytic cell. Patent CN102296328A "A low temperature control method for aluminum electrolysis" proposes a low temperature control method for aluminum electrolysis. The electrolysis temperature during electrolysis is 930-936°C, the lithium carbonate content in the electrolyte is 2.8-3.0% of the electrolyte mass fraction, and the molecular ratio of sodium fluoride to aluminum fluoride in the electrolyte is 2.3-2.5. This patent requires the addition of lithium carbonate to the electrolytic cell. Lithium carbonate is expensive and the cost is extremely high. At the same time, with the addition of lithium carbonate, the solubility performance of alumina is also poor.
[0034] In summary, the above methods all affect the solubility and dissolution rate of A12O3 in the electrolyte. If the dissolution rate is too low, the A12O3 added to the electrolytic cell will not be dissolved and diffused in time, and precipitation will occur at the bottom of the cell, affecting the cell condition.
[0035] The technical solution provided by the embodiment of the present invention is to solve the above technical problems, and the overall idea is as follows:
[0036] In a first aspect, the present application provides a method for reducing the electrolysis temperature of an aluminum electrolysis cell, such as Figure 1 As shown, the method includes:
[0037] By adding additives into the electrolytic cell, the electrolysis temperature of the aluminum electrolytic cell can be reduced;
[0038] The additives include magnesium carbonate and substances containing magnesium carbonate.
[0039] The embodiment of the present application provides a method for reducing the electrolysis temperature of an aluminum electrolysis cell. On the basis of the existing aluminum electrolysis process conditions, the method reduces the temperature of the electrolysis cell by adding at least one of magnesium carbonate and a substance containing magnesium carbonate to the electrolysis cell. The carbon dioxide generated by the decomposition of magnesium carbonate in the electrolysis cell can disturb the electrolyte, which is beneficial to the dissolution of aluminum oxide, thereby solving the problem that the additive for reducing the temperature of the electrolysis cell will cause the solubility of aluminum oxide to deteriorate. Moreover, after magnesium carbonate is converted into magnesium fluoride in the electrolysis cell, it is beneficial to the formation of the furnace wall and the separation of carbon slag, thereby improving the stability of the electrolysis cell.
[0040] As an implementation method of an example of the present application, the content of impurities in the substance containing magnesium carbonate is less than 8 weight %; and the impurities do not include aluminum oxide.
[0041] As a preferred embodiment of the present application, by limiting the content of impurities in the substance containing magnesium carbonate to less than 8% by weight, the content of magnesium carbonate in the additive is relatively high, thereby further ensuring the effect of reducing the electrolysis temperature of the aluminum electrolysis cell. At the same time, it should be understood that in the present application, if the content of impurities in the substance containing magnesium carbonate is greater than 8% by weight, such as the content of impurities in the substance containing magnesium carbonate is 10% by weight, etc., it is still possible to reduce the electrolysis temperature of the aluminum electrolysis cell, but the amount of additives used will increase, and the effect of reducing the electrolysis temperature of the aluminum electrolysis cell will decrease to a certain extent.
[0042] As an implementation of an example of the present application, the substance containing magnesium carbonate includes at least one of magnesite and dolomite.
[0043] In the present application, the content of magnesium carbonate in magnesite and dolomite is relatively high and can be used as an additive.
[0044] As an implementation of an embodiment of the present application, the additive reduces the electrolysis temperature of the aluminum electrolysis cell by lowering the initial crystallization temperature of the electrolyte.
[0045] In the present application, on the basis of the existing aluminum electrolysis process conditions, the method reduces the electrolyte primary crystallization temperature by adding magnesium carbonate and at least one of substances containing magnesium carbonate into the electrolytic cell, thereby achieving the purpose of lowering the electrolysis temperature of the aluminum electrolytic cell, reducing heat dissipation, and improving the utilization rate of electric energy.
[0046] As an implementation method of the embodiment of the present application, the amount X of the additive added and the mass fraction Z of magnesium fluoride in the electrolyte after adding the additive satisfy the relationship 1; the relationship 1:
[0047] Z = X*C1*C2+Z1-Z2;
[0048] Among them, Z represents the amount of additive added; X represents the mass fraction of magnesium fluoride in the electrolyte after adding the additive; C1 represents the mass fraction of magnesium carbonate in the additive; C2 represents the conversion rate constant of each unit of magnesium carbonate into magnesium fluoride; Z1 represents the initial mass fraction of magnesium fluoride in the electrolyte; Z2 represents the mass fraction of magnesium fluoride volatilized in the electrolyte.
[0049] In the present application, at least one of magnesium carbonate and a substance containing magnesium carbonate is added to the electrolytic cell to reduce the temperature of the electrolytic cell; at the same time, after magnesium carbonate is converted into magnesium fluoride in the electrolytic cell, it is beneficial to the formation of the furnace wall and the separation of carbon slag, thereby improving the stability of the electrolytic cell. According to the amount of additive added X, the mass fraction Z of magnesium fluoride in the electrolyte after the aluminum electrolysis process after adding the additive reaches a stable state can be obtained through the above relationship 1; wherein, C1 represents the mass fraction of magnesium carbonate in the additive and Z1 represents the initial mass fraction of magnesium fluoride in the electrolyte, both of which can be measured before aluminum electrolysis; C2 represents the conversion rate constant of each unit of magnesium carbonate converted to magnesium fluoride and Z2 represents the mass fraction of magnesium fluoride volatilized in the electrolyte, which can be obtained by multiple experimental measurements based on different existing aluminum electrolysis processes.
[0050] As an implementation of an embodiment of the present application, the value of C2 is 0.74; the value of Z2 is 0.001 to 0.003.
[0051] In the present application, the inventors have found through research that when the conversion rate constant C2 of each unit of magnesium carbonate converted to magnesium fluoride is calculated as 0.74 and the value of Z2 is 0.001-0.003, the result obtained is highly accurate.
[0052] As an implementation method of the present application, the amount of the additive X and the preset reduction value Y of the electrolysis temperature of the aluminum electrolysis cell satisfy the relationship 2:
[0053] Y=C*X*C1*C2
[0054] Among them, Y represents the preset reduction value of the electrolysis temperature of the aluminum electrolysis cell; C represents the constant of the reduction of electrolyte temperature caused by each unit increase of magnesium fluoride in the electrolyte; X represents the mass fraction of magnesium fluoride in the electrolyte after adding the additive; C1 represents the mass fraction of magnesium carbonate in the additive; C2 represents the conversion rate constant of each unit of magnesium carbonate into magnesium fluoride.
[0055] In the present application, when the electrolyte crystallization temperature (T 初晶 ) is higher than the target crystallization temperature (T 目标 ), the preset lowering value of the electrolysis temperature of the aluminum electrolysis cell (target crystallization temperature (T 目标 ) minus the electrolyte crystallization temperature (T 初晶 ) value), through the relationship 2, the amount of additive added X can be obtained. In other words, in the present application, the amount of additive added X depends on the preset reduction value of the electrolysis temperature of the aluminum electrolysis cell (target initial crystallization temperature (T 目标 ) minus the electrolyte crystallization temperature (T 初晶 ) value).
[0056] As an implementation method of an embodiment of the present application, the value of C is 6 to 7; the value of C2 is 0.74.
[0057] As an implementation method of the present application, the method of adding an additive to the electrolytic cell to reduce the electrolysis temperature of the aluminum electrolytic cell specifically includes:
[0058] According to the preset reduction value Y of the electrolysis temperature of the aluminum electrolysis cell, the addition amount X of the additive is obtained;
[0059] Adding the additive in an amount X to the electrolytic cell in stages to reduce the electrolysis temperature of the aluminum electrolytic cell;
[0060] The amount of additives added multiple times a day in each stage does not exceed 0.15% of the total weight of the electrolyte; the total amount of additives added in each stage does not exceed 2.5% of the total weight of the electrolyte.
[0061] As an implementation manner of the embodiment of the present application, the preset reduction value Y of the electrolysis temperature of the aluminum electrolysis cell is less than 50.
[0062] In the present application, when the electrolyte crystallization temperature (T 初晶 ) is higher than the target crystallization temperature (T 目标 ), the electrolysis temperature (t) is lowered by lowering the electrolyte crystallization temperature, and the target crystallization temperature T 目标 The adjustable range is the original electrolyte crystallization temperature T 初晶 and the target crystallization temperature T 目标 The difference is less than 50°C (the preset reduction value Y of the electrolysis temperature of the aluminum electrolysis cell can be 50°C, 40°C, 30°C, 20°C, etc. in some specific embodiments). The target crystallization temperature (T 目标 ), and then by adding magnesium carbonate or magnesite with high magnesium carbonate content to the electrolytic cell in small amounts and multiple times to reduce T 初 The electrolytic process conditions of the electrolytic cell are gradually adjusted with the addition of magnesium carbonate, according to T 目标 Determine the final amount of magnesium carbonate added. During the addition process, the upper part of the electrolytic cell is gradually kept warm as t decreases. 初晶 Reach T 目标 After that, no more magnesium carbonate was added and the temperature of the electrolytic cell remained stable.
[0063] At the same time, the amount of additives added multiple times a day in each stage (such as 3 times, 4 times, 5 times, etc.) is controlled not to exceed 0.15% of the total weight of the electrolyte; the total amount of additives added in each stage does not exceed 2.5% of the total weight of the electrolyte. The purpose is: if the single amount added in each stage or the total amount added in each stage is too much, it is easy to cause instability of the electrolytic cell, and magnesium carbonate will release gas, which may increase the danger of the aluminum electrolysis production process.
[0064] In summary, the embodiment of the present application provides a method for reducing the electrolysis temperature of an aluminum electrolysis cell, which has at least the following advantages compared with the prior art:
[0065] The additive is low in cost, and the magnesium carbonate reaction releases CO2 gas to disturb the electrolyte, which is beneficial to the dissolution of alumina. The dissolution performance of alumina is guaranteed or even better. After reducing t by this method, the power utilization rate of the electrolytic cell is improved, the anode consumption and heat loss are reduced, and the working environment is improved.
[0066] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.
[0067] Example 1
[0068] A 200kA electrolytic cell, before implementation, the electrolyte composition (wt): NaF 49.00%, KF 4.99%, CaF2 5.00%, MgF2 0.39%, LiF 1.78%, Al2O3 1.82%, AlF3 36.02%, the primary crystallization temperature is 943.6°C, the electrolysis temperature is 946°C, the cell voltage of the electrolytic cell is 4.052V, the heat loss is large due to the high electrolysis temperature, the heat dissipation loss is 1.852V, the current efficiency is 90.8%, the power utilization rate is 48.37%, and the anode consumption is 425kg / t-Al.
[0069] In order to improve the energy utilization rate of the electrolytic cell, we lower the electrolysis temperature by adding the chemical magnesium carbonate into the electrolytic cell.
[0070] The target crystallization temperature is set at 920℃, the electrolyte content in the electrolytic cell is about 15t, and the daily addition amount in the first stage is not more than a certain amount P 11 (0.1%), when the addition amount reaches a certain amount P 12 (1.5%), no addition is done temporarily, the crystallization temperature and composition of the electrolyte in the electrolytic cell are monitored every day, the main process and technical conditions (including: molecular ratio 2.7±0.5, aluminum level 25cm±1, electrolyte level 18cm±1, alumina concentration control (1.5%-3%), the following main process and technical conditions in Example 1 are the same as this time) are controlled unchanged, the electrolytic cell remains stable for 20 days, and the content of magnesium fluoride in the electrolyte component of the electrolytic cell becomes 1.45% on the twentieth day after stopping the addition of magnesium carbonate, and the other components remain basically unchanged, the crystallization temperature drops to 937.3°C, and the electrolysis temperature is 942.4°C at this time. The electrolytic cell is stable, and the second stage of addition is implemented, and the daily addition amount is not more than a certain amount P 21(0.08%), when the addition amount reaches a certain amount P 22 (1.5%) is not added for the time being, and the initial crystallization temperature and composition of the electrolyte in the electrolytic cell are continuously monitored every day. The main process and technical conditions remain unchanged, and the electrolytic cell remains stable for 20 days. On the twentieth day after stopping the addition of magnesium carbonate, the content of magnesium fluoride in the electrolyte component of the electrolytic cell changes to 2.48%, and the other components remain basically unchanged. The initial crystallization temperature drops to 931.6°C, and the electrolysis temperature is 938.8°C at this time. The electrolytic cell is stable, and the third stage of addition is implemented, and the daily addition amount is not more than a certain amount P 31 (0.06%), when the addition amount reaches a certain amount P 32 (1.5%) is not added for the time being, the crystallization temperature and composition of the electrolyte in the electrolytic cell are monitored every day, the main process technical conditions are controlled unchanged, the electrolytic cell remains stable for 20 days, and the content of magnesium fluoride in the electrolyte component of the electrolytic cell changes to 3.56% on the twentieth day after stopping the addition of magnesium carbonate, and the other components remain basically unchanged, the crystallization temperature drops to 925.4℃, and the electrolysis temperature is 933.6℃ at this time. The electrolytic cell is stable, and the fourth stage of addition is implemented. As the crystallization temperature gradually approaches the target, the daily addition amount is not more than a certain amount P 41 (0.05%), monitor the initial crystallization temperature and composition of the electrolyte in the electrolytic cell every day, when the addition amount reaches a certain amount P 42 (1.3%), the initial crystallization temperature reaches 920°C, no more addition is made, the electrolytic cell remains stable, and the content of magnesium fluoride in the electrolyte component of the electrolytic cell changes to 4.47% on the twentieth day after the addition of magnesium carbonate is stopped, and the others remain basically unchanged. At this time, the electrolysis temperature is 928.6°C, the cell voltage is 3.932V, the heat loss is 1.752V, the current efficiency is 92.5%, the power utilization rate is 50.89%, and the anode consumption is 420kg / t-Al. During the whole magnesium carbonate addition process, as the cell temperature decreases, the thickness of the covering material needs to be gradually thickened to increase the upper insulation.
[0071] Example 2
[0072] A 240kA electrolytic cell, before implementation, has the following electrolyte components (wt): NaF 47.17%, KF 1.58%, CaF2 3.95%, MgF2 0.33%, LiF 2.71%, Al2O3 1.15%, AlF3 35.73%, the crystallization temperature is 940.5°C, the electrolysis temperature is 953°C, the cell voltage is 4.073V, the heat dissipation loss is 1.883V, the current efficiency is 90.7%, the power utilization rate is 48.38%, and the anode consumption is 417kg / t-Al.
[0073] In order to improve the energy utilization rate of the electrolytic cell, we added Xiuyan magnesite to the electrolytic cell (the main components of the magnesite purchased this time: MgCO3 96.43%, Al2O3 1.62%, SiO2 0.92%, Fe2O3 0.53%).
[0074] The target crystallization temperature is set at 916°C, the electrolyte content in the electrolytic cell is about 17t, and the daily addition amount in the first stage is not more than a certain amount P 11 (0.08%), when the addition amount reaches a certain amount P 12 (1.6%), no addition is made temporarily, the crystallization temperature and composition of the electrolyte in the electrolytic cell are monitored every day, the main process and technical conditions (including: molecular ratio 2.5±0.5, aluminum level 24cm±1, electrolyte level 17cm±1, alumina concentration control (1.15%-2.5%), the following main process and technical conditions in Example 2 are the same as this time) are controlled unchanged, the electrolytic cell remains stable for 24 days, and the content of magnesium fluoride in the electrolyte component of the electrolytic cell becomes 1.41% on the 24th day after stopping adding magnesite, and the other components remain basically unchanged, the crystallization temperature drops to 933.7°C, and the electrolysis temperature is 942.8°C at this time. The electrolytic cell is stable, and the second stage of addition is implemented, and the daily addition amount is not more than a certain amount P 21 (0.07%), when the addition amount reaches a certain amount P 22 (1.4%) is not added for the time being, and the primary crystallization temperature and composition of the electrolyte in the electrolytic cell are continuously monitored every day. The other process technical conditions, molecular ratio, aluminum level, electrolyte level, and alumina concentration are controlled unchanged. The electrolytic cell remains stable for 22 days. On the 22nd day after stopping adding magnesite, the content of magnesium fluoride in the electrolyte component of the electrolytic cell becomes 2.37%, and the others remain basically unchanged. The primary crystallization temperature drops to 927.9°C, and the electrolysis temperature is 937.3°C at this time. The electrolytic cell is stable, and the third stage of addition is implemented, and the daily addition amount is not more than a certain amount P 31 (0.06%), when the addition amount reaches a certain amount P 32 (1.3%) was not added for the time being, and the crystallization temperature and composition of the electrolyte in the electrolytic cell were monitored every day. The main process technical conditions (including: molecular ratio 2.6±0.5, aluminum level 26cm±1, electrolyte level 16cm±1, alumina concentration control (1.3%-2.5%) were kept unchanged, and the electrolytic cell remained stable for 20 days. On the twentieth day after stopping the addition of magnesium carbonate, the content of magnesium fluoride in the electrolyte component of the electrolytic cell changed to 3.24%, and the others remained basically unchanged. The crystallization temperature dropped to 922.7°C, and the electrolysis temperature was 931.9°C at this time. The electrolytic cell was stable, and the fourth stage of addition was implemented, and the daily addition amount was not more than a certain amount P 41 (0.05%), when the addition amount reaches a certain amount P 42(1.2%) is not added for the time being, and the crystallization temperature and composition of the electrolyte in the electrolytic cell are monitored every day. The main process technical conditions, molecular ratio, aluminum level, electrolyte level, and alumina concentration are controlled unchanged. The electrolytic cell remains stable for 18 days. On the twentieth day after stopping the addition of magnesium carbonate, the content of magnesium fluoride in the electrolyte component of the electrolytic cell becomes 4.06%, and the others remain basically unchanged. The crystallization temperature drops to 917.1°C, and the electrolysis temperature is 926.5°C at this time. The electrolytic cell is stable, and the fifth stage of addition is implemented. As the crystallization temperature gradually approaches the target, the daily addition amount is not more than a certain amount P 51 (0.03%), monitor the initial crystallization temperature and composition of the electrolyte in the electrolytic cell every day, and when the addition amount reaches a certain amount P 52 (0.37%), the primary crystal temperature reaches 916℃, no more addition, the electrolytic cell remains stable, and the electrolyte component magnesium fluoride content in the electrolytic cell changes to 4.28% on the twentieth day after stopping adding magnesite, and the others remain basically unchanged. At this time, the electrolysis temperature is 924.9℃, the cell voltage is 3.889V, the heat loss is 1.726V, the current efficiency is 92.35%, the power utilization rate is 50.23%, and the anode consumption is 413kg / t-Al. During the entire magnesite addition process, as the cell temperature decreases, the thickness of the covering material needs to be gradually thickened to increase the upper insulation.
[0075] Example 3
[0076] A 300kA electrolytic cell, before implementation, has the following electrolyte components (wt): NaF 46.86%, KF 2.08%, CaF2 4.89%, MgF2 0.72%, LiF 4.78%, Al2O3 1.35%, AlF3 36.32%, the crystallization temperature is 925.6°C, the electrolysis temperature is 935°C, the cell voltage is 3.970V, the heat dissipation loss is 1.782V, the current efficiency is 90.2%, the power utilization rate is 49.13%, and the anode consumption is 419kg / t-Al.
[0077] In order to improve the energy utilization rate of the electrolytic cell, we added magnesite from Jianshan area of Xinjiang into the electrolytic cell (the main components of the magnesite purchased this time: MgCO3 97.24%, Al2O3 1.29%, SiO2 0.64%, Fe2O3 0.41% and CaO 0.42%).
[0078] The target crystallization temperature is set at 920°C, the electrolyte content in the electrolytic cell is about 20t, and the daily addition amount in the first stage is not more than a certain amount P 11 (0.03%), when the addition amount reaches a certain amount P 12(1%), no addition was made temporarily, the crystallization temperature and composition of the electrolyte in the electrolytic cell were monitored every day, the main process technical conditions (including: molecular ratio 2.6±0.5, aluminum level 26cm±1, electrolyte level 16cm±1, alumina concentration control (1.3%-2.5%)) were kept unchanged, the electrolytic cell remained stable for 15 days, and the magnesium fluoride content of the electrolyte component in the electrolytic cell changed to 1.37% on the 15th day after stopping adding magnesite, and the others remained basically unchanged, the crystallization temperature dropped to 921.3℃, and the electrolysis temperature was 932.0℃ at this time. The electrolytic cell was stable, and the second stage of addition was implemented. As the crystallization temperature gradually approached the target, the daily addition amount was not more than a certain amount P 21 (0.02%), monitor the initial crystallization temperature and composition of the electrolyte in the electrolytic cell every day, and when the addition amount reaches a certain amount P 22 (0.32%), the primary crystal temperature reaches 920℃, no more addition, the electrolytic cell remains stable, and the electrolyte content of magnesium fluoride in the electrolytic cell changes to 1.55% on the twentieth day after stopping adding magnesium carbonate, and the others remain basically unchanged. At this time, the electrolysis temperature is 929℃, the cell voltage is 3.953V, the heat loss is 1.773V, the current efficiency is 90.6%, the power utilization rate is 49.43%, and the anode consumption is 417kg / t-Al. During the whole process of adding magnesite, as the cell temperature decreases, the thickness of the covering material needs to be gradually thickened to increase the upper insulation.
[0079] Example 4
[0080] A 500kA electrolytic cell, before implementation, has the following electrolyte components (wt): NaF 45.52%, KF 6.02%, CaF2 3.73%, MgF2 0.24%, LiF 1.70%, Al2O3 1.72%, AlF3 32.31%, the crystallization temperature is 939.6°C, the electrolysis temperature is 948.8°C, the cell voltage is 3.967V, the heat dissipation loss is 1.796V, the current efficiency is 91.5%, the power utilization rate is 49.81%, and the anode consumption is 420kg / t-Al.
[0081] In order to improve the energy utilization rate of the electrolytic cell, we added Kuandian magnesite to the electrolytic cell (the main components of the magnesite purchased this time: MgCO3 96.61%, Al2O3 1.44%, SiO2 0.75%, Fe2O3 0.68% and CaO0.52%).
[0082] The target crystallization temperature is set at 918°C, the electrolyte content in the electrolytic cell is about 34t, and the daily addition amount in the first stage is not more than a certain amount P 11 (0.06%), when the addition amount reaches a certain amount P 12(2%), no addition was made temporarily, the crystallization temperature and composition of the electrolyte in the electrolytic cell were monitored every day, the main process technical conditions (including: molecular ratio 2.8±0.5, aluminum level 32cm±1, electrolyte level 15cm±1, alumina concentration control (1.5%-2.5%)) were kept unchanged, the electrolytic cell remained stable for 25 days, and the magnesium fluoride content of the electrolyte component in the electrolytic cell changed to 1.61% on the 25th day after stopping the addition of magnesite, and the others remained basically unchanged, the crystallization temperature dropped to 931.7℃, and the electrolysis temperature was 942.2℃ at this time. The electrolytic cell was stable, and the second stage of addition was implemented, and the daily addition amount was not more than a certain amount P 21 (0.05%), when the addition amount reaches a certain amount P 22 (1.8%) is not added for the time being, and the primary crystallization temperature and composition of the electrolyte in the electrolytic cell are continuously monitored every day. The other process technical conditions, molecular ratio, aluminum level, electrolyte level, and alumina concentration are controlled unchanged. The electrolytic cell remains stable for 30 days. On the 30th day after stopping adding magnesite, the content of magnesium fluoride in the electrolyte component of the electrolytic cell becomes 2.85%, and the others remain basically unchanged. The primary crystallization temperature drops to 924.0℃, and the electrolysis temperature is 934.9℃ at this time. The electrolytic cell is stable, and the third stage of addition is implemented, and the daily addition amount is not more than a certain amount P 31 (0.04%), monitor the initial crystallization temperature and composition of the electrolyte in the electrolytic cell every day, and when the addition amount reaches a certain amount P 32 (1.43%), the initial crystallization temperature reached 918°C, no more addition was made, the electrolytic cell remained stable, and the content of magnesium fluoride in the electrolyte component of the electrolytic cell changed to 3.83% on the twentieth day after the addition of magnesium carbonate was stopped. At this time, the initial crystallization temperature was 918°C, the electrolysis temperature was 926.5°C, the electrolytic cell voltage was 3.906V, the heat loss was 1.713V, the current efficiency was 91.94%, the power utilization rate was 50.63%, and the anode consumption was 416kg / t-Al. During the entire magnesite addition process, as the cell temperature decreases, the thickness of the covering material needs to be gradually thickened to increase the upper insulation.
[0083] Example 5
[0084] A 500kA electrolytic cell, before implementation, has the following electrolyte components (wt): NaF 50.04%, KF 1.26%, CaF2 3.88%, MgF2 0.26%, LiF 1.43%, Al2O3 2.08%, AlF3 40.91%, the crystallization temperature is 954.6°C, the electrolysis temperature is 961.4°C, the cell voltage is 4.03V, the heat dissipation loss is 1.863V, the current efficiency is 90.5%, the power utilization rate is 48.82%, and the anode consumption is 424kg / t-Al.
[0085] In order to improve the energy utilization rate of the electrolytic cell, we add the chemical magnesium carbonate into the electrolytic cell.
[0086] The target crystallization temperature is set at 919°C, the electrolyte content in the electrolytic cell is about 34t, and the daily addition amount in the first stage is not more than a certain amount P 11 (0.05%), when the addition amount reaches a certain amount P 12 (1.7%), no addition was made temporarily, the primary crystallization temperature and composition of the electrolyte in the electrolytic cell were monitored every day, the main process technical conditions (including: molecular ratio 2.45±0.5, aluminum level 29cm±1, electrolyte level 17cm±1, alumina concentration control (2%-3%)) were kept unchanged, the electrolytic cell remained stable for 30 days, and the electrolyte content of magnesium fluoride in the electrolytic cell became 1.46% on the 30th day after stopping adding magnesite, and the others remained basically unchanged, the primary crystallization temperature dropped to 947.8℃, and the electrolysis temperature was 955.0℃ at this time. The electrolytic cell was stable, and the second stage of addition was implemented, and the daily addition amount was not more than a certain amount P 21 (0.04%), when the addition amount reaches a certain amount P 22 (1.5%) is not added for the time being, and the initial crystallization temperature and composition of the electrolyte in the electrolytic cell are continuously monitored every day. The other process technical conditions, molecular ratio, aluminum level, electrolyte level, and alumina concentration are controlled unchanged. The electrolytic cell remains stable for 28 days. On the 28th day after stopping the addition of magnesium carbonate, the content of magnesium fluoride in the electrolyte component of the electrolytic cell becomes 2.52%, and the others remain basically unchanged. The initial crystallization temperature drops to 941.2°C, and the electrolysis temperature is 948.4°C at this time. The electrolytic cell is stable, and the third stage of addition is implemented, and the daily addition amount is not more than a certain amount P 31 (0.04%), when the addition amount reaches a certain amount P 32 (1.4%) is not added for the time being, the crystallization temperature and composition of the electrolyte in the electrolytic cell are monitored every day, the main process conditions remain unchanged, the electrolytic cell remains stable for 25 days, and the content of magnesium fluoride in the electrolyte component of the electrolytic cell changes to 3.50% on the 25th day after stopping the addition of magnesium carbonate, and the other components remain basically unchanged, the crystallization temperature drops to 935.5℃, and the electrolysis temperature is 943.8℃ at this time. The electrolytic cell is stable, and the fourth stage of addition is implemented, and the daily addition amount is not more than a certain amount P 41 (0.04%), when the addition amount reaches a certain amount P 32 (1.3%) is not added for the time being, and the crystallization temperature and composition of the electrolyte in the electrolytic cell are monitored every day. The main process technical conditions, molecular ratio, aluminum level, electrolyte level, and alumina concentration are controlled unchanged. The electrolytic cell remains stable for 25 days. On the 25th day after stopping the addition of magnesium carbonate, the content of magnesium fluoride in the electrolyte component of the electrolytic cell becomes 4.42%, and the others remain basically unchanged. The crystallization temperature drops to 930.1°C, and the electrolysis temperature is 939.5°C at this time. The electrolytic cell is stable, and the fifth stage of addition is implemented, and the daily addition amount is not more than a certain amount P 51 (0.03%), when the addition amount reaches a certain amount P 52(1.2%) is not added for the time being, and the crystallization temperature and composition of the electrolyte in the electrolytic cell are monitored every day. The main process technical conditions, molecular ratio, aluminum level, electrolyte level, and alumina concentration are kept unchanged. The electrolytic cell remains stable for 23 days. On the 23rd day after stopping the addition of magnesium carbonate, the content of magnesium fluoride in the electrolyte component of the electrolytic cell becomes 5.27%, and the others remain basically unchanged. The crystallization temperature drops to 925.4°C, and the electrolysis temperature is 933.7°C at this time. The electrolytic cell is stable, and the sixth stage of addition is implemented, and the daily addition amount is not more than a certain amount P 61 (0.03%), when the addition amount reaches a certain amount P 62 (1.2%) is not added for the time being, and the crystallization temperature and composition of the electrolyte in the electrolytic cell are monitored every day. The main process technical conditions, molecular ratio, aluminum level, electrolyte level, and alumina concentration are controlled unchanged. The electrolytic cell remains stable for 23 days. On the 23rd day after stopping the addition of magnesium carbonate, the content of magnesium fluoride in the electrolyte component of the electrolytic cell becomes 6.12%, and the others remain basically unchanged. The crystallization temperature drops to 920.5°C, and the electrolysis temperature is 929.2°C at this time. The electrolytic cell is stable, and the fourth stage of addition is implemented. As the crystallization temperature gradually approaches the target, the daily addition amount is not more than a certain amount P 41 (0.01%), monitor the initial crystallization temperature and composition of the electrolyte in the electrolytic cell every day, and when the addition amount reaches a certain amount P 42 (0.25%), the initial crystal temperature reaches 919°C, no more addition, the electrolytic cell remains stable, and the content of magnesium fluoride in the electrolyte component of the electrolytic cell changes to 6.26% on the twentieth day after stopping adding magnesium carbonate, and the others remain basically unchanged. At this time, the electrolysis temperature is 927.8°C, the cell voltage is 3.931V, the heat loss is 1.737V, the current efficiency is 91.86%, the power utilization rate is 50.23%, and the anode consumption is 418kg / t-Al. During the whole magnesium carbonate addition process, as the cell temperature decreases, the thickness of the covering material needs to be gradually thickened to increase the upper insulation.
[0087] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0088] In the present application, in the absence of any contrary description, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present specification, the terms "including", "comprising", etc. refer to "including but not limited to". In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of the associated objects, indicating that there may be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A, B can be singular or plural. In this article, "at least one" refers to one or more, and "plural" refers to two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of singular or plural items. For example, "at least one of a, b, or c", or "at least one of a, b and c", can both mean: a, b, c, ab (i.e. a and b), ac, bc or abc, where a, b, c can be single or plural, respectively.
[0089] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A method for reducing the electrolysis temperature of an aluminum electrolysis cell, characterized in that: The method comprises: According to the preset reduction value Y of the electrolysis temperature of the aluminum electrolysis cell, the addition amount X of the additive is obtained; Adding the additive in an amount X to the electrolytic cell in stages to reduce the electrolysis temperature of the aluminum electrolytic cell; The additive is a substance containing magnesium carbonate, and the additive reduces the electrolysis temperature of the aluminum electrolysis cell by reducing the initial crystallization temperature of the electrolyte; The amount of the additive added X and the mass fraction Z of magnesium fluoride in the electrolyte after adding the additive satisfy the relationship 1; the relationship 1: Z= X*C1*C2+Z1-Z2; The amount of the additive added X and the preset reduction value Y of the electrolysis temperature of the aluminum electrolysis cell satisfy the relationship 2: Y = C*X*C1*C2; Among them, C1 represents the mass fraction of magnesium carbonate in the additive; C2 is a constant of 0.74; Z1 represents the initial mass fraction of magnesium fluoride in the electrolyte; Z2 represents the mass fraction of magnesium fluoride volatilized in the electrolyte, and the value of Z2 is 0.001~0.003, and C is a constant of 6~7; The total amount of additives added multiple times per day in each stage shall not exceed 0.15% of the total weight of the electrolyte; the total amount of additives added in each stage shall not exceed 2.5% of the total weight of the electrolyte.
2. The method for reducing the electrolysis temperature of an aluminum electrolysis cell according to claim 1, characterized in that: The content of impurities in the material containing magnesium carbonate is less than 8% by weight; and the impurities do not include aluminum oxide.
3. The method for reducing the electrolysis temperature of an aluminum electrolysis cell according to claim 1, characterized in that: The substance containing magnesium carbonate includes at least one of magnesite and dolomite.
4. The method for reducing the electrolysis temperature of an aluminum electrolysis cell according to claim 1, characterized in that: The aluminum electrolysis cell electrolysis temperature is preset to have a reduction value Y < 50.
Citation Information
Patent Citations
A method for low-temperature control in aluminum electrolysis
CN102296328A
Preparation method of lead electrobath for transitting to electrolysis in low termperature
CN1873057A
Method for improving alumina dissolution rate in aluminium electrolysis process
CN102312252A